Efficiency Level Analysis of Mini Purse Seine Fisheries Business Based on Small Pelagics in Moti District, Ternate City - Agung R. Djufri (CV Projurnal Mitra Publikasi, 2025)
North Maluku is an archipelagic province with great potential for small pelagic fisheries resources, especially in Moti Island which is included in Fisheries Management Area (WPP) 715. However, the utilisation of these resources has not been optimal and the Mini Purse Seine fishery business activities still face various obstacles such as limited facilities, high fuel prices, and low fish selling prices. This study aims to analyse the technical factors of production that affect catches, assess the level of efficiency of Mini Purse Seine fisheries, and provide recommendations for business improvement in Moti District, Ternate City. Data were collected through surveys, interviews, and literature studies, with Principal Component Regression and Data Envelopment Analysis (DEA) approaches using SPSS 26 and SBFA 4.0 software. The results showed that vessel size, duration of fishing, fuel, engine capacity, length of fishing gear, number of crew members, and number of trips affected the catch by 82.6%. There are 3 technically efficient business units, 4 near efficient units, and 2 inefficient units. Recommendations for improvement include reducing operational and investment costs, increasing production and profits, and reducing the number of crew members for certain units. This research provides a basis for more efficient and sustainable management policies in support of improving the welfare of fishermen on Moti Island.